2021
DOI: 10.1208/s12248-021-00595-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ontogeny Functions for Renal Transporters Using a Combined Population Pharmacokinetic and Physiology-Based Pharmacokinetic Approach: Application to OAT1,3

Abstract: To date, information on the ontogeny of renal transporters is limited. Here, we propose to estimate the in vivo functional ontogeny of transporters using a combined population pharmacokinetic (popPK) and physiology-based pharmacokinetic (PBPK) modeling approach called popPBPK. Clavulanic acid and amoxicillin were used as probes for glomerular filtration, combined glomerular filtration, and active secretion through OAT1,3, respectively. The predictive value of the estimated OAT1,3 ontogeny function was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…40 In addition, Sînziana Cristea found that the transporters in the kidneys gradually mature with age, reaching half that of the adult levels at approximately 7 months of age and adult levels at 15 years. 41 Through the simulations run in our study, we also found that the PStc values gradually increase with age in the kidneys, reaching half that of adult levels at around 2−11 years of age and adult levels at 12−16 years. Therefore, we presumed that the PStc values might change with age, which could come from differences in the active transporters that were not directly included in the model, although this needs to be further proved in the future.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…40 In addition, Sînziana Cristea found that the transporters in the kidneys gradually mature with age, reaching half that of the adult levels at approximately 7 months of age and adult levels at 15 years. 41 Through the simulations run in our study, we also found that the PStc values gradually increase with age in the kidneys, reaching half that of adult levels at around 2−11 years of age and adult levels at 12−16 years. Therefore, we presumed that the PStc values might change with age, which could come from differences in the active transporters that were not directly included in the model, although this needs to be further proved in the future.…”
Section: Discussionsupporting
confidence: 61%
“…The study by Sînziana Cristea indicated that the transporters in the kidneys gradually mature with age, reaching half that of adult levels around 7 months of age and adult levels at 15 years. 41 However, no transporters have been reported to be related with PGB secretion and reabsorption in the kidneys. Therefore, we paid more attention to CL filt .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the ontogeny of renal transporters was studied in a wide age range of pediatric subjects using mRNA and protein abundance, the results indicate renal drug transporters exhibit different rates and patterns of maturation 13 . The results from a later study, 41 based on in vivo data using a combined population PK and PBPK approach, on the hybrid OAT1/OAT3 ontogeny agrees for these transporters. However, in another study, the authors reported little significant age‐related abundance changes (age >1 year) for many renal transporters 35 .…”
Section: Discussionmentioning
confidence: 99%
“…PBPK models can provide quantitative predictions of drug disposition in children by mechanistically representing relevant physiological processes from the population of interest 9,10 . PBPK models incorporating pediatric renal clearance have included the ontogeny of glomerular filtration and tubular secretion, and these approaches have demonstrated superior predictability compared with allometric scaling in children less than 2 years of age 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…9,10 PBPK models incorporating pediatric renal clearance have included the ontogeny of glomerular filtration and tubular secretion, and these approaches have demonstrated superior predictability compared with allometric scaling in children less than 2 years of age. [11][12][13] Although these efforts have incorporated a measure of tubular secretion and RT ontogeny, transporter-specific ontogeny profiles that span the pediatric age spectrum to include preterm neonates are still needed. 14 Ideally, these profiles would provide estimates of the distributions of RT activity to facilitate pediatric population PBPK model predictions.…”
Section: Introductionmentioning
confidence: 99%